Мифологические и фантастические мотивы в произведениях Вильяма Шекспира и Джона Китса - Акбарова, Ч.У. (Культура народов Причерноморья, 2014)
В статье прослеживается как в творчестве В. Шекспира и Дж. Китса отразились
мифологические и фантастические мотивы Античности. У статті простежується як у творчості В. Шекспіра та Дж. Кітса відбилися міфологічні
та фантастичні мотиви Античності. The paper traces how mythological and fantastic motifs of Antiquity reflected in the works of
W. Shakespeare and J. Keats.
In the Renaissance and Romanticism, classical Greek mythology appears often in works of famous authors of the
time, such as William Shakespeare and John Keats. In famous plays of Shakespeare and Keats we can find not
only mythological characters, but also fantastic: in “Venus and Adonis”, Shakespeare uses classical
mythological / fantastic characters such as Venus, Adonis etc.; in “A Midsummer’s Night Dream” – Theseus
and Hippolyta; Pyramus and Thisbe; Oberon, Titania and Puck / Robin Goodfellow; Peaseblossom, Cobweb,
Moth, Mustardseed, fairies and spirits, etc.; in “Hamlet” – the ghost; in “Julius Caesar” – Caesar's ghost; in
“Macbeth” – Hecate, Three witches, Banquo’s ghost, etc.; in “The Tempest”, he uses – Iris, Ceres, and Juno;
Prospero, Sycorax, Caliban, Ariel; and other plays; Keats: in “Endymion” we find classical mythological /
fantastic characters and names such as Endymion, Dryope, Apollo, Lucifer etc.; in “Hyperion” – Hyperion,
Titans, Achilles, Saturn, Phantoms, Tellus etc.; in “Isabella and the Pot of Basil” – Theseus, the ghost, the
Monster, Melpomene etc.